Impact of Biologic Treatment of Crohn’s Disease on the Rate of Surgeries and Other Healthcare Resources: An Analysis of a Nationwide Database From Poland - Holko, Przemysław; Kawalec, Paweł; Pilc, Andrzej (Frontiers in Pharmacology, 2018)
Background. There is conflicting evidence on the impact of biologic treatment on the rate of complications and surgeries in Crohn’s disease (CD). We aimed to assess real-world consequences of biologic treatment of CD. Methods. All adult patients with CD treated with infliximab and adalimumab in the years 2012–2014 were identified from the database of the National Health Fund in Poland. Mixed models were used to assess the impact of biologics on medical resource utilization by comparing the periods before and after the first use of biologics (pre-index vs post-index). The additional analyses including quintile of total exposure to biologic treatment were performed. Results. Data on 1393 patients (age, 31.9 years; males, 52.6%) were analyzed over a median of 1064 days (range: 71, 1148). During the post-index period patients received from 1 to 4 treatments with biologic agents (maximum allowed period of 12 months per treatment). We observed a reduction in the rates of surgeries (by 27%, p=0.001), hospitalizations for CD excluding surgical procedures (by 45%, p<0.001), as well as consumption of antibiotics (by 31%, p<0.001) and steroids (by 35%, p<0.001 in the post-index compared with the pre-index period. The reduction in the rate of surgeries, hospitalizations for CD, and steroid intake increased with the increase of exposure to biologic agents. Conclusions. Biologic treatment changed the management patterns by lowering the rate of surgeries and other healthcare resources related to complications or worsening of CD. The reduction in the resource utilization was dependent on the level of exposure to treatment, suggesting that limitation of the treatment period itself may be inadequate.